Malaria infection and Entomological Survey of Anopheline Species in Some Communities in Ila Local Government Area of the State of Osun, Nigeria - Oyewole, Isaac; Mustapha, Abdur-Rahman Kolawole; Adeogun, Adedapo; Awolola, Taiwo Samson (British Journal of Healthcare and Medical Research, 2022)
A cross-sectional survey of the population of mosquitoes and incidence of malaria was carried out in Iyana-Ofa Community and some selected villages around the College campus (College Community) in Ila Local Government Area, State of Osun, Nigeria for a period of one year (dry and rainy seasons). Mosquitoes were collected using the aspirator tube and pyrethrum spray catch (PSC). Morphological and PCR methods were used for identification. ELISA was employed to determine circum-sporozoite antigens of Plasmodium falciparum. Human biting rate (HBR) was determined to calculate the Entomological inoculation rate (EIR). Blood film examination using Giemsa staining techniques was used to detect malaria parasites in the blood of 427 participants. A Thick film was used to determine the density of the malaria parasite. Out of 946 mosquitoes collected, 605 (64%) were Anopheles gambiae. No significant difference in mosquito population density (p>0.05) from the study communities. EIR from the study areas was moderately high and no significant difference was observed. P. falciparum predominates among participants positive for malaria parasites. Parasite density ranged from 100 to 4,000 parasite/µl blood, the mean parasite density generally declined with age while that 51-60 yr recorded the least. There was no significant difference in the malaria infection rates in the two communities (P>0.05), but there was a correlation between the mosquito population density and the prevalence of malaria. This study provides baseline information necessary to formulate effective control interventions in the area.